SMARTPHONE UTILIZATION AND REPRODUCTIVE HEALTH KNOWLEDGE AMONG ADOLESCENTS: A CROSS-SECTIONAL STUDY IN ACEH BESAR REGENCY, INDONESIA - Nurbaiti; Anita Anita; Irma Seriana; Lia lajuna; Yushida (International Archives of Medical Sciences and Public Health, 2026)
Adolescent reproductive health remains a major public health concern, particularly in developing countries where access to accurate information is often limited. This study examined the association between smartphone utilization and reproductive health knowledge among female adolescents in Aceh Besar, Indonesia. A quantitative cross-sectional study was conducted in May 2025 involving 81 female students selected through proportional stratified random sampling. Data were collected using structured questionnaires and analyzed using binary logistic regression. Overall, 72.8% of respondents used smartphones to access reproductive health information, and 55.6% had good reproductive health knowledge. Smartphone use for reproductive health information was significantly associated with good knowledge (OR = 2.98; 95% CI: 1.33-6.67; p = 0.001). Duration of smartphone use (p = 0.004) and social media platform (p = 0.006) were also significantly associated with knowledge. Smartphones may serve as effective channels for improving reproductive health knowledge among female adolescents, although causal relationships cannot be established due to the cross-sectional design.